The future of Global Environmental Assessments: 20 years after the Millennium Ecosystem Assessment - Elena Michele Bennett; Walter Reid; Stephen Carpenter; Tom Dietz; Garry Peterson; Neville Ash; T Doug Beard; Silke Beck; Reinette Biggs; Noel Castree; John Ehrmann; Tim Forsyth; et al. (Current Opinion in Environmental Sustainability, 2026)

Rethinking the science-policy interface for chemicals, waste, and pollution: Challenging core assumptions - Jen Iris Allan; Anwesha Borthakur; Fiona Kinniburgh; Moritz Petersmann; Angeliki Balayannis; Andrew Barry; Silke Beck; Kevin Elliott; Tim Forsyth; Anita Hardon; Hannah Hughes; Philip Macnaghten; et al. (Global Environmental Change, 2025)

Animal social networks are robust to changing association definitions - Alex Hoi Hang Chan; Jamie Dunning; Kristina B Beck; Terry Burke; Heung Ying Janet Chik; Daniel Dunleavy; Tim Evans; André Ferreira; Babette Fourie; Simon C. Griffith; Friederike Hillemann; Julia Schroeder (Behavioral Ecology and Sociobiology, 2025)
The interconnecting links between individuals in an animal social network are often defined by discrete, directed behaviours, but where these are difficult to observe, a network link (edge) may instead be defined by individuals sharing a space at the same time, which can then be used to infer a social association. The method by which these associations are defined should be informed by the biological significance of edges, and therefore often vary between studies. Identifying an appropriate measure of association remains a challenge to behavioural ecologists. Here, we use automatically recorded feeder visit data from four bird systems to compare three methods to identify a social association: (1) strict time-window, (2) co-occurrence in a group, and (3) arrival-time. We tested the similarity of the resulting networks by comparing the repeatability and sensitivity of individuals’ social traits (network degree, strength, betweenness). We found that networks constructed using different methods but applying similar, ecologically relevant definitions of associations based on individuals’ spatio-temporal co-occurrence, showed similar characteristics. Our findings suggest that the different methods to construct animal social networks are comparable, but result in subtle differences driven by species biology and feeder design. We urge researchers to carefully evaluate the ecological context of their study systems when making methodological decisions. Specifically, researchers in ecology and evolution should carefully consider the biological relevance of an edge in animal social networks, and the implications of adopting different definitions.

Properties of outer solar system pebbles during planetesimal formation from meteor observations - Peter Jenniskens; Paul R. Estrada; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; et al. (Icarus, 2024)

Lifetime of cm-sized zodiacal dust from the physical and dynamical evolution of meteoroid streams - Peter Jenniskens; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; Solvay Blomquist; et al. (Icarus, 2024)

What potential does the EU Single-Use Plastics Directive have for reducing plastic pollution at coastlines and riversides? An evaluation based on citizen science data - Tim Kiessling; Mandy Hinzmann; Linda Mederake; Sinja Dittmann; Dennis Brennecke; Marianne Böhm-Beck; Katrin Knickmeier; Martin Thiel (Waste Management, 2023)

Research Priorities for Achieving Healthy Marine Ecosystems and Human Communities in a Changing Climate - Whitney R. Friedman; Benjamin S. Halpern; Elizabeth McLeod; Michael W. Beck; Carlos M. Duarte; Carrie V. Kappel; Arielle Levine; Robert D. Sluka; Steven Adler; Casey C. O’Hara; Eleanor J. Sterling; Sebastian Tapia-Lewin; et al. (Frontiers in Marine Science, 2020)

Small mammal species richness is directly linked to regional productivity, but decoupled from food resources, abundance, or habitat complexity - Christy M. McCain; Sarah R. B. King; Tim Szewczyk; Jan Beck (Journal of Biogeography, 2018)
Aim Species richness is often strongly correlated with climate. The most commonly invoked mechanism for this climate‐richness relationship is the more‐individuals‐hypothesis ( MIH ), which predicts a cascading positive influence of climate on plant productivity, food resources, total number of individuals, and species richness. We test for a climate‐richness relationship and an underlying MIH mechanism, as well as testing competing hypotheses including positive effects of habitat diversity and heterogeneity, and the species‐area effect. Location Colorado Rocky Mountains, USA : two elevational gradients in the Front Range and San Juan Mountains. Methods We conducted standardized small mammal surveys at 32 sites to assess diversity and population sizes. We estimated vegetative and arthropod food resources as well as various aspects of habitat structure by sampling 20 vegetation plots and 40 pitfall traps per site. Temperature, precipitation and net primary productivity ( NPP ) were assessed along each gradient. Regressions and structural equation modelling were used to test competing diversity hypotheses and mechanistic links predicted by the MIH . Results We detected 3,922 individuals of 37 small mammal species. Mammal species richness peaked at intermediate elevations, as did productivity, whereas temperature decreased and precipitation increased with elevation. We detected strong support for a productivity‐richness relationship, but no support for the MIH mechanism. Food and mammal population sizes were unrelated to NPP or mammal species richness. Furthermore, mammal richness was unrelated to habitat diversity, habitat heterogeneity, or elevational area. Main conclusions Sites with high productivity contain high mammal species richness, but a mechanism other than a contemporary MIH underlies the productivity–diversity relationship. Possibly a mechanism based on evolutionary climatic affiliations. Protection of productive localities and mid‐elevations are the most critical for preserving small mammal richness, but may be decoupled from trends in population sizes, food resources, or habitat structure.

De novo FBXO11 mutations are associated with intellectual disability and behavioural anomalies - Daniel Fritzen; Alma Kuechler; Mona Grimmel; Jessica Becker; Sophia Peters; Marc Sturm; Hela Hundertmark; Axel Schmidt; Martina Kreiß; Tim M. Strom; Dagmar Wieczorek; Tobias B. Haack; et al. (Human Genetics, 2018)

Anti-necrotic and cardioprotective effects of a cytosolic renin isoform under ischemia-related conditions - Heike Wanka; Doreen Staar; Philipp Lutze; Barbara Peters; Johanna Hildebrandt; Tim Beck; Inga Bäumgen; Alexander Albers; Thomas Krieg; Katrin Zimmermann; Jaroslaw Sczodrok; Simon Schäfer; et al. (Journal of Molecular Medicine, 2016)

Mouse, man, and meaning: bridging the semantics of mouse phenotype and human disease - John M. Hancock; Ann-Marie Mallon; Tim Beck; Georgios V. Gkoutos; Chris Mungall; Paul N. Schofield (Mammalian Genome, 2009)

COMPARISON OF THE CAPABILITIES OF DUGONGS AND WEST INDIAN MANATEES TO MASTICATE SEAGRASSES - Helene Marsh; Cathy A. Beck; Tim Vargo (Marine Mammal Science, 1999)